Integrated Environmental Study for Beach Management: A Methodological Approach - Francesca Palmisani; Mauro Fabiano; Gabriella Camarsa; Rosanna Dursi; Roberta Ivaldi; Valentina Marin (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper aims to present a project convened by the University of Genoa and Fondazione Eni Enrico Mattei (FEEM), in collaboration with Local Authorities, concerning the development of tools for beach management in the Riviera del Beigua (Liguria Region, Italy). The aim of the first step of the project is to assess the environmental state of resort beaches examining them interdisciplinary, through a data analysis based on a sound understanding of the components of the physical and the human system. The following step will be the treatment of the data, through the use of various instruments, which use a synthesis analysis, such as the traditional SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis, and the use of a set of environmental and socio-economic indicators. Finally, our ultimate target is to propose guidelines, which will supply an instrument to back up policies concerning beach planning and management.
Keywords: Q20; Q26; 330; Costal management; Sustainable tourist; Integrated assessment; Indicators